Yearbook of Chinese theology 2015 - Huang, Baoluo. (Yearbook of Chinese Theology, 2015)
The Yearbook of Chinese Theology is an international, ecumenical and fully peer-reviewed series on Chinese theology in English. Its main focus is on interdisciplinary, contextual, and cross-cultural studies in the areas of Biblical Studies, Church History, Systematic Theology, Practical Theology, and Comparative Religions. The Yearbook also features articles exploring wider issues in church and society. The Yearbook of Chinese Theology thus meets the growing demand for the study of the new academic discipline of Christianity in a Chinese context. In this first volume, harmony and Sinicization of Christianity in China are studied from a systematic theological viewpoint. Confucian Ruism and the Human-God relationship are investigated from a practical theological perspective. Articles on the rebellious Taiping tianguo movement and on a Fujian Catholic community shed light on the history of Christianity in China, and two articles draw attention to the Bible in relation to literature and general public. Furthermore, a review of the Protestant Church is offered from the viewpoint of Civil Society construction, and Chinese contemporary ideology and historical Nestorianism are researched using methodology derived from the field of Comparative Religions. This volume offers genuine Chinese theological research, which was previously unavailable in English, by top scholars in the study of Christianity in China.